Impact of the COVID-19 pandemic on the returns of Real Estate Investment Traded Funds (REITs) FTSE Nareit Index Study (period of 2019-2021) - boutarfa, Rachid; mahrez, Salah (Journal of Research in Finance and Accounting, 2023)
This study aimed to evaluate the financial performance of REITs funds that were affected by the repercussions of the (Covid-19) pandemic, both qualitatively and geographically, based on the (FTSE NAREIT ALL REITS) index, which provides data and evaluations for real estate investors that are of great importance in making their investment decisions. Because REITs distribute a percentage of at least 90% of net profits, making them attractive to investors, especially since the underlying assets are income generating. In order to achieve the objectives of the study, we relied on the analytical descriptive approach that is appropriate to the nature of the subject, and the study reached results, the most important of which are: sectors such as technology, data centers, and health achieved positive results compared to shopping centers, hotels and resorts that were severely affected by the general closure, and the America region witnessed the best returns compared to other regions.